2019
DOI: 10.4239/wjd.v10.i1.37
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes in the Kokan region of India

Abstract: BACKGROUND BKL Walawalkar Hospital is situated near the village of Dervan in the Kokan region of the state of Maharashtra in India. A survey of 2200 surrounding villages showed 51.8% adults had body mass index (BMI) below <18.5 kg/m 2 and only 4.5% were overweight. A survey of 11521 adolescent girls from rural schools showed 64% prevalence of thinness. In the same region, government survey reported the prevalence of diabetes around 7%, and 70% prevalence of leanness. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…36,37 In our study, obesity was not associated with DM. Different concepts have been reported for obesity and DM, such as general obesity, 8 BMI, 30,38 the duration of obesity and body fat distribution 7 and waist circumference for men and BMI for women. 5,31 However, a controversial suggestion has been that obesity protects against DM because of the presence of anti-diabetogenic effects of fat tissues in some obese patients, 39 or genetic factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…36,37 In our study, obesity was not associated with DM. Different concepts have been reported for obesity and DM, such as general obesity, 8 BMI, 30,38 the duration of obesity and body fat distribution 7 and waist circumference for men and BMI for women. 5,31 However, a controversial suggestion has been that obesity protects against DM because of the presence of anti-diabetogenic effects of fat tissues in some obese patients, 39 or genetic factors.…”
Section: Discussionmentioning
confidence: 99%
“…29 The association between DM and a family history of DM has been observed in India. 30,31 Generally, the association between a family history of DM and DM suggests shared genetic or environmental factors in the aetiology of DM. 32 Our study and the previous study in Sudan 28 showed no association between sex and DM.…”
Section: Discussionmentioning
confidence: 99%